2022
DOI: 10.1097/cm9.0000000000002036
|View full text |Cite
|
Sign up to set email alerts
|

Risk of gestational diabetes recurrence and the development of type 2 diabetes among women with a history of gestational diabetes and risk factors: a study among 18 clinical centers in China

Abstract: Background:Gestational diabetes mellitus (GDM) brings health issues for both mothers and offspring, and GDM prevention is as important as GDM management. It was shown that a history of GDM was significantly associated with a higher maternal risk for GDM recurrence. The incidence of GDM recurrence was unclear because of the incidence of second-child was low before 2016 in China. We aim to investigate the prevalence of GDM recurrence and its associated high-risk factors which may be useful for the prediction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…[46] And the degree of abnormal glucose metabolism in previous pregnancy was important in the recurrence of diabetes mellitus in pregnancy. [35] Our result was consistent with another meta-analysis that concluded that shorter intervals (less than 2 years) are not associated with an increased risk of recurrent preeclampsia, but longer intervals appear to increase the risk. [7] We further found that the estimated risk of preeclampsia or eclampsia, gestational hypertension, and diabetes mellitus in pregnancy for women with long IPIs increased more among women with a previous term birth than among those with a previous preterm birth or an infant with a gestational age less than 28 weeks.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…[46] And the degree of abnormal glucose metabolism in previous pregnancy was important in the recurrence of diabetes mellitus in pregnancy. [35] Our result was consistent with another meta-analysis that concluded that shorter intervals (less than 2 years) are not associated with an increased risk of recurrent preeclampsia, but longer intervals appear to increase the risk. [7] We further found that the estimated risk of preeclampsia or eclampsia, gestational hypertension, and diabetes mellitus in pregnancy for women with long IPIs increased more among women with a previous term birth than among those with a previous preterm birth or an infant with a gestational age less than 28 weeks.…”
Section: Discussionsupporting
confidence: 92%
“…However, gestational diabetes mellitus took account of approximately 90% of diabetes mellitus in pregnancy. [ 34 , 35 ] Thus, we defined diabetes mellitus in pregnancy in this research, which refers to pre-existing diabetes mellitus and diabetes mellitus arising in pregnancy.…”
Section: Methodsmentioning
confidence: 99%
“…A history of GDM is associated with a higher risk of GDM recurrence in subsequent pregnancies. Also, these people have a higher chance of developing type 2 diabetes in the future [72,73]. Further, it is widely accepted that women with a history of GDM are at increased risk of other metabolic diseases and also developing cardiovascular diseases [74].…”
Section: >Insert: Table2mentioning
confidence: 99%
“…Gestational diabetes mellitus (GDM) is a specific type of diabetes that affects women during pregnancy who were not diagnosed with diabetes before pregnancy [1] . Women with prior GDM will have a high risk of recurrent GDM after the first pregnancy and postpartum metabolic disorders [2–5] . GDM itself may be associated with a series of adverse pregnancy outcomes including preeclampsia, macrosomia, preterm delivery, and primary cesarean section [6,7] .…”
Section: Introductionmentioning
confidence: 99%
“…[1] Women with prior GDM will have a high risk of recurrent GDM after the first pregnancy and postpartum metabolic disorders. [2][3][4][5] GDM itself may be associated with a series of adverse pregnancy outcomes including preeclampsia, macrosomia, preterm delivery, and primary cesarean section. [6,7] Previous studies have shown that both b cell function and insulin sensitivity may be involved in the pathogenesis of GDM.…”
Section: Introductionmentioning
confidence: 99%